Bilateral Japan-Chile Relations (1990-1997): Against Uncertainty, the Strategic Alliance [Relaciones Bilaterales Japón-Chile (1990-1997): Contra la Incertidumbre, la Alianza Estratégica] - Toro-Ibacache, L (Arturo Prat University, 2020)
This paper aims to understand and explain the factors that prompted an economic powerhouse like Japan to propose a strategic alliance with Chile in 1994. The hypothesis is that Chilean financial stability in the 1990s and an opportunity for the Japanese to access the MERCOSUR economies were the factors that drove this alliance. However, the impact of the Asian financial crisis in 1997, which led Japan to be replaced by China as the primary market for Latin American exports in Asia, prevented this idea from materializing as it was originally meant to. In response, a series of high-level official visits took place between the countries, which highlighted the gap between Chile’s foreign policy agenda and the interests of the country’s business sector. © The Authors.